THE RELATIONSHIP KNOWLEDGE AND ATTITUDE OF WOMEN COUPLE OF REPRODUCTIVE AGE (PUS) WITH PAPSMEAR EXAMINATION IN PANOBEIAN PANE HEALTH CENTER SIMALUNGUN DISTRICT - Hendri Kurniawan; Dilla Sastia Mara; Muhartri Sanjaya (International Conference on Health Science, Green Economics, Educational Review and Technology, 2021)
Pap Smear is an attempt to take fluid from the vagina to see cells around the cervix (Setiati, 2009). Pap Smear is a screening for cervical (cervical) cancer performed by midwives or obstetricians. This examination aims to find out the presence of HPV or a series of carcinomas that cause cervical cancer (Parahita, 2012). xx Research Objectives to determine the relationship between knowledge and attitudes of women of reproductive age couples (PUS) with Pap smear examination at the Panombeian Panci Health Center, Simalungun Regency in 2017. This type of research is Analytic with Cross sectional approach. The population of this study were all couples of childbearing age (PUS) who came to the Panomberan Panci Health Center in 2017.